Determinação da política ótima de manutenção em sistemas reparáveissujeitos a manutenções imperfeitas - Cristiane Bastos Lopes (2012)
The present work aims to propose an economic model of maintenance in repairable systems based on the analysis of a model proposed in the literature by Liao et al (2010). It starts with a briefreview of concepts related to reliability, as well as the concept of time value of money. Then, it presents the model proposed by Liao et al (2010) and the questionable points, followed by the development of two models (A and B). The first one, built with the propositions of Liao et al (2010), and the second one, including the value of money over time. The results were substantially different from those obtained by Liao et al (2010). The effects of some individual cost parameters on the optimal policy are studied, as well as the impact of uncertainty in the estimation of those parameters for determining the most important cost component. As expected, the inclusion of the time value of the money leads to change in the optimal maintenance policy.